The Influence of Tour Guides' Communication Competence on The Satisfaction of German Asian Trails Indonesian Tourists - Brahmantya Agung Priharjuna; Putu Ayu Aryasih; Ida Bagus Putu Puja (J-TRUE: Journal of Travel and Leisure, 2025)
This study analyses the influence of tour guides' communication competence on German tourists' satisfaction at Asian Trails Indonesia. Communication competence is divided into two dimensions: verbal and non-verbal. The research was conducted at PT. Asian Trails Indonesia office in Denpasar, Bali, with data collection from January to May 2025. The research used a quantitative approach with a saturated sampling technique of 120 German tourists. Data was collected through questionnaires with a Likert scale of 1-5. Data analysis used multiple linear regression with SPSS version 26. The results showed that: (1) Verbal communication competence has a positive and significant effect on German tourists' satisfaction with a t-value of 9.061 and significance of 0.000; (2) Non-verbal communication competence has a positive and significant effect on German tourists' satisfaction with a t-value of 4.281 and significance of 0.000. The coefficient of determination value (adjusted R²) of 0.705 indicates that 70.5% of the variation in tourist satisfaction can be explained by the tour guides' verbal and non-verbal communication competence.